Teacher education for the 21st century : creativity, aesthetics and ethics in preparing teachers for our future - Blumenfeld-Jones, Donald (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
This book is for anyone interested in how to build a teacher education program utilizing the arts as one central modality for teaching and learning or for those interested in building some of their program along these lines. Throughout the book you will find reference to the intersection of ethics, aesthetics, and teaching. We provide an integrated program devoted to good learning and the good society.In the book we discuss how the program came to be and the underlying educational thinking that informs the whole program. This section of the book is invaluable for understanding how the reader can build her/his own arts approach to teacher education. The central section of the book is devoted to the specific coursework of the program. Each author describes in detail how she/he leverages aesthetics and art to expand the possibilities of learning and teaching (including a chapter focused on the core competency course, Teaching, Imagination, Creativity) in language and literacy, psychology of education, science education, mathematics education, social studies education, and classroom management including many examples from our teaching. The book ends with a focus group discussion about the program by former students.
Keywords: Teachers -- Training of.; Teaching -- Moral and ethical aspects.; Creative thinking -- Study and teaching.; Aesthetics.; Art in education.; Teaching -- Philosophy.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books